TINJAUAN KRIMINOLOGI TENTANG KEJAHATAN DENGAN KEKERASAN TERHADAP PEREMPUAN - Faikah, Nur (An - Nisa`, 2011)
Crime Is one form of behavioral aberrations that always hit the norms of life that exist in society. One of the paling prone and vulnerable to violent crime are woman. Therefore, investigation against crime never stops conducted by criminology. This indicates that the problem of crime against woman is a central issue throughout human life.The types of violent crimes are often experienced by woman is rape, mugging in public, assault, murder, sexual or other harassment. Therefore, seeing the complexity of violent crime that is often experienced by woman will require special attention to address among others the seriousness of law enforcement agencies especially the police in order to try everything to combat violent crimes against woman through preventive efforts in the form of guidance, awareness and education before turmoil of evil, while the repressive effort is the eradication of crime is going on indiscriminately.